ROLE-PLAY IN ENGLISH COURSE CLASSROOMS: OPPORTUNITIES AND CONSTRAINTS FOR SPEAKING PRACTICE (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the opportunities and constraints of implementing role-play as a speaking practice technique in a non-formal English course “EEC” in Sidoarjo city, Indonesia. Using a descriptive qualitative design, the study focuses on beginner level learners who initially demonstrated low motivation and limited confidence when speaking English. Data were collected through classroom observation during a role-play session and short post-activity interviews. Findings indicate that role-play created opportunities for (1) increased willingness to speak, (2) more expressive and spontaneous interaction, and (3) improved learning engagement because students experienced speaking as a meaningful social task rather than a test of grammatical accuracy. At the same time, constraints emerged, including limited vocabulary, frequent pauses before speaking, short speaking turns (approximately 15 seconds per role), uneven participation (dominant versus passive learners), and ongoing grammar and pronunciation issues. The study argues that role-play can function as a supportive bridge from controlled speaking to more authentic communication for beginners, but it requires deliberate scaffolding such as pre-task vocabulary support, clear role cards, confidence-building routines, and teacher feedback that prioritize intelligibility and interaction. Practical implications are offered for course teachers who aim to maximize speaking time, balance participation, and reduce anxiety during communicative practice.